Home-made cheese preservation using sodium alginate based on edible film incorporating essential oils - Mahcene, Zineb; Khelil, Aminata; Hasni, Sara; Bozkurt, Fatih; Goudjil, Mohamed Bilal; Tornuk, Fatih (SPRINGER INDIA, 2021)
Abstact The objective of the present study is developing a new technique for the preservation of natural cheese by the use of an edible biofilm based on sodium alginate in order to evaluate the effect of the essential oils (O. basilicum L, R. officinalis L. A. herba alba Asso. M. pulegiumL.) incorporated in the film on the oxidation stability, microbial spoilage, physicochemical characteristics and sensory criteria. The cheese samples coated with sodium alginate incorporated by the oils showed moderate stability in terms of oxidative stabilities of proteins and lipids during storage. In addition, poor microbial growth (total aerobic mesophilic flora, yeasts and fecal coliforms) was observed in cheese samples coated with biofilm, also, the growth ofStaphylococci Salmonellaand Molds for all types of cheese were completely inhibited. Additionally, it was observed that the biofilm coating reduced the weight loss and hardness of the cheese comparing with the uncoated sample. The results of sensory analysis revealed that uncoated cheese, coated with sodium alginate and sodium alginate composed of oil ofO. basilicumwere the most preferred by panelists, in comparison with others. Therefore, it was concluded that this technique of coating cheese with edible film activated with essential oils is preferred and favorable by virtue of the effect of oils preserving the cheese without seriously affecting their organoleptic properties.
Keywords: Home-made cheese; Preservation; Active film; Sodium alginate; Essential oils; SHELF-LIFE; CHEMICAL-COMPOSITION; ANTIOXIDANT; CHITOSAN; IMPROVE; QUALITY; STORAGE; HYDROSOLS; COATINGS; OREGANO; Food Science & Technology